The Role of Justice in Fin-Tech Performance: The analysis of Maqasid al-Syariah Index - Osman, Adibah Alawiah; Abdullah, Azwan; Ab Rahman, Siti Maziah; Safian, Sharul Shahida Shakrein; Ibrahim, Nor Zawani Mamat; Shaharuddin, Norhasimah (Advances in Social Sciences Research Journal, 2024)
The essence of justice is how well a person harmonizes with what is right. It is clear that justice is one of the principles of exalted ethics, especially in terms of Shariah compliance, since the Quran and Sunnah provide a solid basis for justice. Integrating Islamic Finance knowledge with Islamic Ethics is crucial for holistically assessing Shariah compliance in the world of Finance Technology (FIN-TECH). In terms of justice, numerous prior researchers have done most of the work. In this study, secondary data was gathered from Islamic financial institutions of specified sectors regarding the Maqasid al-Syariah Index on justice. The partial least squares structural equation modeling (PLS-SEM) method was the main statistical technique employed in this study. This study aimed to offer a precise mode in which justice may influence the performance Fin-Tech in Islamic Finance’s success. The study of justice plays a significant role in guiding the direction of Fin-Tech in Islamic Finance applications.